Uji Stabilitas Fisik dan Kimia Tablet Paracetamol dengan Berbagai Variasi Bahan Pengikat - Muhammad Reihan Ridha; Muhammad Romansyah Khatami; Nor Latifah (An-Najat, 2025)
Tablets represent one of the most widely utilized solid pharmaceutical dosage forms, in which both physical and chemical stability parameters play a critical role in ensuring product quality and therapeutic efficacy throughout the shelf life. The stability of tablet formulations is influenced by various factors, including the type and concentration of binders used during manufacturing. This review aims to evaluate the effects of natural binders—specifically durian seed starch, cempedak seed starch, and mucilage from Dioscorea esculenta (lesser yam) tuber starch—on the quality of paracetamol tablets based on findings from the scientific literature. A systematic literature search was conducted using various academic databases. The reviewed studies revealed that all tested natural binders generally met the physical quality parameters outlined in the Indonesian Pharmacopoeia. However, increasing binder concentrations was associated with prolonged disintegration times and reduced solubility of the active pharmaceutical ingredient (API). These findings highlight the importance of selecting appropriate binder types and optimizing their concentrations to ensure effective drug release and maintain formulation stability during storage.